2021
DOI: 10.18521/ktd.880762
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Attitudes of Family Physicians Towards the COVID-19 Vaccine

Abstract: This study has aimed to reveal the opinions of family physicians on the COVID-19 vaccine. Methods: The data collection forms prepared for this cross-sectional study were converted into an online questionnaire form and sent to the physicians working as family physicians in different provinces of Turkey between December 2020 -January 2021 via emails (GoogleGroups) and communication groups (Facebook, WhatsApp, etc.). The responses of 494 family physicians in Turkey, who were accessible through this method and vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Bulca et al stated that the married physicians developed a more positive attitude towards COVID-19 vaccines in their study among family physicians. 25 These findings are similar to our study, and it can be thought that this is due to the concern of healthcare professionals that may transmit the infection to their families. Zigron et al showed that there is a positive correlation between unemployment status and willingness to vaccine in their study involving 506 dentists.…”
Section: Discussionsupporting
confidence: 91%
“…Bulca et al stated that the married physicians developed a more positive attitude towards COVID-19 vaccines in their study among family physicians. 25 These findings are similar to our study, and it can be thought that this is due to the concern of healthcare professionals that may transmit the infection to their families. Zigron et al showed that there is a positive correlation between unemployment status and willingness to vaccine in their study involving 506 dentists.…”
Section: Discussionsupporting
confidence: 91%